PUBLIC POLICIES OF SPORTS (Fiep Bulletin - online, 2011)
This literature review aims to present some concepts and discussions on Public Policies for Sport. This is part of a monograph study still under construction. We started initially from the conceptualization of terms such as Public Policy, Public Administration and Public Policies for Sport, to develop after a review of the Public Policies and the decentralization process of Sport.
Keywords: Public Policy; Public Administration and Public Policy Sports